Retroperitoneal Abscess After Laparoscopic Cholecystectomy - Macedo Peña, Víctor (2000)
Accidental rupture of gallbladder during laparoscopic cholecystectorny associated with escape of its content to intraabdominal space is a non-infrequent event. Surgeons worry about potential complications this event could trigger. lt has been reported abscess formation, infections, inflammation, fibrosis, adhesions, etc. We present a case of a feverish patient with malaise, leukocytosis and history of laparoscopic cholecystectorny. Preoperative diagnosis was mixed retroperitoneal mass vs. retroperitoneal abscess. During the surgery we confirmed the second suspection. We suggest surgeons should take precautions to remove all the gallstones from peritoneal space. Also, they should be alert about abdominal pain in patients with previous laparoscopic cholecystectorny.